2009
DOI: 10.1089/scd.2008.0235
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Increases CXCR4 Expression in Hematopoietic Stem/Progenitor Cells by Chromatin Remodeling

Abstract: A major limitation of cord blood (CB) hematopoietic stem/progenitor cell (HSPC) transplantation in adult patients is the low cell dose available, which is associated with delayed or failed engraftment. This has prompted intensive research to develop novel strategies to improve HSPC engraftment and reconstitution. The chemokine receptor CXCR4 and its ligand stromal cell-derived factor (SDF)-1alpha play a crucial role in the homing and repopulation capacity of HSPCs. We hypothesized that in HSPCs the CXCR4 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…24 In contrast, Gul et al showed that VPA increased CXCR4 expression and migration toward a CXCL12 gradient in hematopoietic stem/progenitor cells (HSPCs) 25 ; moreover, Gul reported that VPA repressed CXCR4 expression and chemotaxis in more differentiated CD34-negative AML (acute myelogenousleukemic) cells, but increased CXCR4 expression and chemotaxis in immature CD34-positive AML cells. 26 Another HDI, trichostatin A (TSA), transiently increased CXCR4 expression after 24 h treatment, but downregulated it after 48 h in melanoma cells.…”
Section: Pan Et Al Demonstrated Thatmentioning
confidence: 98%
“…24 In contrast, Gul et al showed that VPA increased CXCR4 expression and migration toward a CXCL12 gradient in hematopoietic stem/progenitor cells (HSPCs) 25 ; moreover, Gul reported that VPA repressed CXCR4 expression and chemotaxis in more differentiated CD34-negative AML (acute myelogenousleukemic) cells, but increased CXCR4 expression and chemotaxis in immature CD34-positive AML cells. 26 Another HDI, trichostatin A (TSA), transiently increased CXCR4 expression after 24 h treatment, but downregulated it after 48 h in melanoma cells.…”
Section: Pan Et Al Demonstrated Thatmentioning
confidence: 98%
“…MSC migration toward ischemic brain lesions is mediated by the interaction between stromal cellderived factor 1a (SDF-1a), a molecule endowed with potent chemotactic activity, and its specific a-chemokine receptor CXC-chemokine receptor 4 (CXCR4) , in which expression in hematopoietic stem cells is enhanced by VPA (Gul et al, 2009). Because MSC migration is regulated by the Wnt signaling pathway in which activation inhibits GSK3b (Neth et al, 2006), lithium's ability to inhibit GSK3b allows it to activate the Wnt downstream signaling pathway.…”
Section: F Augmented Protective Effects By Lithium and Vpa Cotreatmentmentioning
confidence: 99%
“…This approach is based on the hypothesis that prior attempts to expand HSCs ex vivo using serum-containing (SC) media and cytokine combinations actually result in the silencing of HSC genetic programs (2,7,9,17,(26)(27)(28)(29)(30)(31). This alternative strategy is consistent with the growing evidence that epigenetic mechanisms play important roles in determining whether an HSC undergoes symmetrical divisions and generates additional stem cells, asymmetrical divisions that at best maintain HSC numbers while generating hematopoietic progenitor cells (HPCs), or symmetrical commitment divisions that deplete HSC numbers and generate greater numbers of HPCs (26,27,(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%